Recopilación De Experiencias En La Práctica Pedagógica A Través De La Obra Teatral “El Tesoro” (2014)
This document reveals the elaboration of an academic process, which was developed in the course of the exercise of pedagogical practices, beginning with a shower of ideas for the construction of a theatrical dramaturgy, composed based on the language daily routine used in the school and university environment, managing to complete this process dramaturgical with the play called “El Tesoro”, in it we observe a global problem that seeks to make students reflect, through a staging that contributes to the acting training of its participants.